Perceived supervisor support dan job insecurity dengan change engagement pada karyawan Badan Usaha Milik Negara: Menguji peran mediasi self-efficacy: Perceived supervisor support and job insecurity with change engagement in employees of State-Owned Enterprises: Testing the mediating role of self-efficacy - Musa, Nurmuliasneny; Fajrianthi, Fajrianthi; Sami’an, Sami’an (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2023)
This writing aims to find out whether there is a correlation between perceived supervisor support and job insecurity on change engagement and self-efficacy as a mediator variable for Indonesian BUMN employees. This research involved 351 employees of state-owned companies who were determined using accidental sampling techniques. The research instrument used four scales, namely the Change Engagement Scale, the short version of the Scale of Perceived Supervisor Support (SPSS), the short version of the Job Insecurity Scale (JIS), and the Occupational Self Efficacy Short Version Scale. Data analysis in this writing uses path analysis using Jamovi. Based on the results of data analysis, there is a direct and indirect influence between perceived supervisor support on change engagement through self-efficacy, but there is no significant direct or indirect influence of job insecurity on change engagement through self-efficacy. The results of this research can be a reference for companies, especially BUMN regarding the importance of change engagement and other factors in intervening in organizations and employees.